Altered serum human cytomegalovirus microRNA levels are common and closely associated with the inflammatory status in patients with fever - Wang, Cheng; Zhu, Yunhua; Chen, Penglu; Wang, Chen; Zhou, Wanqing; Zhang, Cuiping; Wang, Jing; Chen, Xi; Ding, Meng; Zhang, Chunni; Wang, Jun-Jun; Zhang, Chen-Yu (Frontiers in Immunology, 2022)
Background: Fever has a complicated etiology, and diagnosing its causative factor is clinically challenging. Human cytomegalovirus (HCMV) infection causes various diseases. However, the clinical relevance, prevalence, and significance of HCMV microRNAs (miRNA) in association with fever remain unclear. In the present study, we analyzed the HCMV miRNA expression pattern in the serum of patients with fever and evaluate its clinical associations with occult HCMV infection status in immune disorders. Methods: We included serum samples from 138 patients with fever and 151 age-gender-matched controls in this study. First, the serum levels of 24 HCMV miRNAs were determined using a hydrolysis probe-based stem-loop quantitative reverse transcription polymerase chain reaction (RT-qPCR) assay in the training set. The markedly altered miRNAs were verified in the validation and testing sets. The serum HCMV IgG/ IgM and DNA titers in the testing cohort were also assessed using enzyme-linked immunosorbent assay (ELISA) and RT-qPCR, respectively. Results: The majority of HCMV miRNAs were markedly upregulated in the serum of fever patients. We selected the five most significantly altered HCMV miRNAs: hcmv-miR-US4-3p, hcmv-miR-US29-3p, hcmv-miR-US5-2-3p, hcmv-miR-UL112-3p, and hcmv-miR-US33-3p for validation. These miRNAs were also significantly elevated in the serum of fever patients in the validation and testing sets compared with the controls. Logistic regression analysis revealed that the five miRNAs were novel potential risk factors for fever. Notably, the serum levels of four of the five confirmed HCMV miRNAs were significantly associated with blood C-reaction protein concentrations. Moreover, the five HCMV miRNA levels were closely correlated with the HCMV DNA titers in the testing cohort. Conclusion: HCMV infection and activation are common in fever patients and could be novel risk factors for fever. These differentially expressed HCMV miRNAs could enable HCMV activation status monitoring in immune disorders.